Quantificação de ingredientes farmacêuticos em um analgésico comercial por Ressonância Magnética Nuclear - Thomazini, Leonardo (Universidade Federal de São Carlos, 2024)
Nuclear Magnetic Resonance (NMR) is a powerful analytical technique used in various fields, such as polymer chemistry, food, and pharmaceuticals, being both a qualitative and quantitative technique. The quantitative use of the technique requires adjustment of some parameters, such as the relaxation delay time between pulses, D1, so that the spins have time to return to the thermal equilibrium state. NMR is a technique capable of analyzing mixtures without the need for separation. One of the methods used is called 'spin chromatography,' or DOSY, which can be useful in the analysis of drugs, as they may contain more than one component. Besides DOSY, techniques such as TOCSY and HSQC-TOCSY were also used for the identification, especially of the excipient signals. The analysis of pharmaceuticals is highly regulated, and in Brazil, this role is assigned to ANVISA, with the rules described in the Brazilian Pharmacopoeia. This work deals with the qualitative and quantitative NMR analysis of the commercial analgesic, focusing on its components, dipyrone, caffeine, and isometheptene. Using DOSY, the signals were assigned as follows: 7.46 ppm to dipyrone, 7.98 ppm to caffeine, and 1.13 ppm to isometheptene. These signals were used for integration and for calculating the mass of each component. One of the samples showed degradation, with calculated values for the three components below the expected levels. In the other two samples, dipyrone and caffeine were within the expected range, while isometheptene was lower than expected.
Quantification of pharmaceutical ingredients in a commercial analgesic by Nuclear Magnetic Resonance
Keywords: Ressonância Magnética Nuclear; RMN; RMN quantitativo; RMNq; Fármacos; CIENCIAS EXATAS E DA TERRA::QUIMICA